1998
DOI: 10.1046/j.1432-1327.1998.2520408.x
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric structure of the repressor of the bacteriophage Mu early operon

Abstract: The regulation of the lytic and lysogenic development in the life cycle of bacteriophage Mu is regulated in part by its repressor, c, which binds to three operator sites, O1, O2 and O3, overlapping two divergent promoters. The oligomeric structure of this repressor protein was investigated by hydrodynamic and biochemical methods. Size-exclusion chromatography, analytical ultracentrifugation, dynamic light scattering, crosslinking and direct electron microscopy observations suggest that c exists primarily as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…32 PRepNK and an unlabeled repressor protein were first mixed and allowed to incubate for 10 mins at 37°C before addition of 1 g trypsin. Digestion was allowed to proceed at the same temperature for 1 h, and then reactions were stopped by the addition of phenylmethylsulfonyl fluoride to 2% (w/v) final concentration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 PRepNK and an unlabeled repressor protein were first mixed and allowed to incubate for 10 mins at 37°C before addition of 1 g trypsin. Digestion was allowed to proceed at the same temperature for 1 h, and then reactions were stopped by the addition of phenylmethylsulfonyl fluoride to 2% (w/v) final concentration.…”
Section: Methodsmentioning
confidence: 99%
“…trans-Targeting proteins such as Vir may function to expose such a determinant in Rep to promote its degradation. The self-associating property of repressor molecules, which exists in solution as a hexamer or higher order oligomer (32,33), may promote Rep-Vir interactions for this process.…”
mentioning
confidence: 99%
“…Even after considering other possible values for (p) and [] (37), our calculations indicated that cWHOLE only varied from 8.6 to 10.3 ns. More importantly, correlation times are longer for larger molecules or complexes, which would have more restricted motion, and Mu repressor is known to exist in hexameric and even higher order oligomeric forms in solution (41,42). Such oligomeric complexes would make up a complex of at least 130 kDa; therefore, the cWHOLE of the repressor protein is more likely 54 ns or more.…”
Section: Methodsmentioning
confidence: 99%
“…cWHOLE would be longer for larger molecules or complexes, which would rotate more slowly. Since the repressor is known to assume a hexameric or higher order oligomeric structure in solution (41,42), the rotational correlation time is most likely 54 ns or greater. However, FIGURE 5.…”
Section: Vir Not Only Promotes Exposure Of Ctd5 But Also Increases Itmentioning
confidence: 99%
“…The product of the c gene of bacteriophage Mu encodes a 196‐residue transposition repressor (Krause and Higgins, 1986; Leung et al ., 1989; Mizuuchi and Mizuuchi, 1989) that is a ClpX substrate (Welty et al ., 1997). It exists in solution as a hexamer or higher order oligomers (Rousseau et al ., 1996; Alazard et al ., 1998), a property that may be important not only for its cooperative binding to Mu operator DNA (Vogel et al ., 1991) but also for communication of conformational states between repressor isoforms (Marshall‐Batty and Nakai, 2003). Mu repressor regulates the decision between lysogeny and lytic development; degradation or inactivation of the Mu repressor leads to expression of transposition functions MuA and MuB, promoting Mu DNA synthesis through replicative transposition.…”
Section: Introductionmentioning
confidence: 99%